Pengaruh Collaboration Branding dan Kualitas Produk terhadap Keputusan Pembelian Sepatu Compass di Kota Surabaya - Zona Icashya Sugara; Ugy Soebiantoro (Jurnal Riset Pendidikan Ekonomi, 2026)
This study ams to analyze the influence of collaboration branding and product quality on the purchasing decisions of Compass shoes in Surabaya. The research is motivated by the increasing competition in the local fashion industry and the collaborative strategies implemented by the Compass brand to expand market share and strengthen consumer loyalty. The method used is descriptive quantitative with a survey approach through questionnares distributed to 96 respondents, who are consumers of Compass shoes in Surabaya. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the assistance of SmartPLS software. The results show that collaboration branding and product quality have a positive and significant impact on the purchasing decisions of Compass shoes. These findings emphasize the importance of well-planned collaborative marketing strategies and consistent product quality improvements to enhance competitiveness and consumer purchase decisions. This research offers practical contributions for brand management in formulating effective and sustanable marketing strategies in the local fashion market.